Collective identity and the coalescence of an expert occupational community: The case of the Canadian tax profession - Hahn, Till‐Arne; Himick, Darlene (Contemporary Accounting Research, 2026)
Abstract Although the community of tax professionals is a key actor in the tax realm, its nature continues to remain elusive in many countries. Using a qualitatively driven mixed‐methods approach that integrates the insights obtained from in‐depth interviews and the results of a survey of practitioners, we examine the Canadian tax field. Although tax work has traditionally been dominated by lawyers and accountants, our study finds that a distinct expert occupation has taken shape, as evidenced by the collective identification of those working full‐time in the area. Theoretically, we show how individuals can effectively generate an occupational community through their collective identification with it and how professions that do not fit the ideal type or that are in the process of emerging may be understood. The concepts of boundary erasure and boundary emergence are introduced as variants of boundary blurring and boundary making to explain how boundaries in a professional field may be reconfigured, allowing for the emergence and informal closure of occupations. Advancing the understanding of occupational groups that have not yet embraced the professional project, our study offers insight into why some forms of expertise might not professionalize in the traditional way. Overall, the findings have implications for research on tax professionals as well as for efforts to govern their work.